The economic costs, management and regulation of biological invasions in the Nordic countries - Kourantidou Melina; Verbrugge Laura N. H.; Haubrock Phillip J.; Cuthbert Ross N.; Angulo; Elena; Ahonen Inkeri; Cleary Michelle; Falk-Andersson Jannike; Granhag Lena; Gislason Sindri; Kaiser Brooks; et al. (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
A collective understanding of economic impacts and in particular of monetary costs of biological invasions is lacking for the Nordic region. This paper synthesizes findings from the literature on costs of invasions in the Nordic countries together with expert elicitation. The analysis of cost data has been made possible through the InvaCost database, a globally open repository of monetary costs that allows for the use of temporal, spatial, and taxonomic descriptors facilitating a better understanding of how costs are distributed. The total reported costs of invasive species across the Nordic countries were estimated at $8.35 billion (in 2017 US$ values) with damage costs significantly outweighing management costs. Norway incurred the highest costs ($3.23 billion), followed by Denmark ($2.20 billion), Sweden ($1.45 billion), Finland ($1.11 billion) and Iceland ($25.45 million). Costs from invasions in the Nordics appear to be largely underestimated. We conclude by highlighting such knowledge gaps, including gaps in policies and regulation stemming from expert judgment as well as avenues for an improved understanding of invasion costs and needs for future research.